SISTEM PAKAR DIAGNOSA PENYAKIT SAPI SEBAGAI UPAYA PENCEGAHAN PENYEBARAN WABAH PMK DI LAMONGAN - Moh. Rosidi Zamroni; Qabilah Cita K. N. S; Agung Wahyudi (JURNAL ILMIAH INFORMATIKA, 2022)
On May 5, 2022, Indonesia was hit by an outbreak of PMK in livestock. Until now, in August 2022, there are 20 provinces, 215 districts/cities, 1,808 sub-districts and 7,434 villages that are still actively infected with nail and mouth disease (PMK). The emergence of PMK is an epidemic that results in huge losses to cattle farmers. Especially if you do not have knowledge about the transmission of the disease. One of the efforts to prevent the spread of livestock disease is to implement an expert system for diagnosing cattle disease using the forward chaining method. Where this system will help farmers to provide knowledge of disease symptoms and diagnosis of disease, so that farmers are able to take initial action to handle their livestock.